Elastic properties of ascending aorta in women with previous pregnancy complicated by early‐ or late‐onset pre‐eclampsia. (11th February 2016) - Orabona, R.; Sciatti, E.; Vizzardi, E.; Bonadei, I.; Valcamonico, A.; Metra, M.; Frusca, T.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2016; 47: 279–279 ABSTRACT: Objectives: To evaluate the elastic properties of the ascending aorta in women with a previous pregnancy complicated by early‐onset (EO) or late‐onset (LO) pre‐eclampsia (PE) and the correlation with gestational age (GA), systolic/diastolic blood pressure (SBP/DBP) and mean uterine artery pulsatility index (UtA‐PI) at diagnosis of the disease as well as with birth weight of the neonate. Methods: Thirty women who had a previous pregnancy complicated by EO‐PE, 30 with a previous pregnancy complicated by LO‐PE and 30 normal controls were selected retrospectively from our electronic database and then recalled for assessment from 6 months to 4 years after delivery. Data regarding GA, SBP/DBP and mean UtA‐PI at the diagnosis of PE were obtained from medical records. At our assessment, aortic M‐mode and tissue Doppler imaging (TDI) parameters were measured. Aortic diameters were assessed at end‐diastole at four levels: Valsalva sinuses, sinotubular junction, tubular tract and aortic arch. Aortic compliance, distensibility, stiffness index (SI), Peterson's elastic modulus (EM), pulse‐wave velocity and M‐mode strain were calculated using standard formulae. Aortic expansion velocity, early and late diastolic retraction velocities and peak systolic tissue strain (TDI‐ϵ) were determined. Results: Aortic diameters at the four levels were significantly greater in both EO‐PE and LO‐PE groups than in controls. Aortic compliance and distensibility and TDI‐ϵ were lower in EO‐PE than in LO‐PE ( P  =  0.001, P  =  0.002 and P  =  0.011, respectively) and controls ( P  =  0.037, P  =  0.044 and P  =  0.013, respectively). SI and EM were higher in EO‐PE than in LO‐PE ( P   = 0.001 and P   < 0.001, respectively) and than in controls ( P  = 0.035 and P  =  0.036, respectively). Multivariate analysis showed GA, DBP and UtA‐PI at diagnosis of PE to be independent predictors of aortic elastic properties. Conclusions: Elastic properties of the ascending aorta were altered in women with a previous pregnancy complicated by EO‐PE, but not in those with LO‐PE. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.